Capacitive Tuning of High Selective T-Shaped Band-Stop Filter: Theory and Experiment - Amit K. Sahu; Dhruba C. Panda; Rajeev K. Parida (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2024)
Article This paper develops an easy design analysis for a simple high selective T-shaped band-stop filter (BSF) loaded with a capacitance. It applies the developed design theory to obtain an appropriate capacitance value for tuning the cut-off frequency. This paper clearly explains the design mechanism for such a simple tunable BSF using ABCD matrices. Simulated filters loaded with capacitances (up to 1.1 pF) show a change in rejection frequencies from 2 GHz (un-tuned) down to 1.047 GHz with 50dB rejection and around 36% -3dB fractional bandwidth. It also shows the effect on pass frequencies which change from 1 GHz down to 111 MHz, while the separation between pass and stop frequency remains around 1 GHz. Measurements on fabricated prototypes match the simulation and theory for tunable frequencies closely. It also compares the performance of the filter with previously reported similar structures.